Electroconductivity of anion-radical TCNQ salts containing cations [M(bipy)₃]²⁺ (M-Fe, Ni or Zn) - Vasylets, G.Y.; Khotkevich, A.V.; Bukrinev, A.S.; Krasnyi, A.S.; Starodub, V.A.; Starodub, V.A.; Kravchenko, A.A.; Medviediev, V.V. (Functional Materials, 2015)
Electrical resistance temperature dependence of three TCNQ anion-radical salts of complex composition containing cations [M||(bipy)₃]²⁺ (M-Fe, Ni or Zn, bipy - 2,2′-dipyridil) have been studied. Measurements have been performed in the range 180-300 K on tableted samples. The compound exhibit semiconducting properties and undergo the Peierls transition. Specific resistance at room temperature is of 7.7 Ω·cm for Fe containing salt and 2.3·10⁻² Ω·cm and 2.5·10⁻² Ω·cm for salts containing Ni and Zn, respectively.